Tempo de inundação da Ilha de Sirituba (Abaetetuba, PA) - ARAÚJO, Cláudia Viana (2018)
This work contributes to studies of water level and tide co-oscillation effects over the floodplain, considering tide effects as main forcing factor on the region. Tides consists of sea level variations caused by astronomical forcing. Their propagation on an estuary results mainly from its own oscillatory movement and river flow on the estuary mouth. On the Abaetetuba islands region, few localities are characterized as terra firme forests, since the majority of the area is prone to floods from seasonal river overflows and daily tide co-oscillations. This set of factors leads to predominance of várzea forests on the estuary. The main river encompassing the Abaetetuba municipality is Pará River, thus prevailing its physical and dynamic patterns. The present study takes place on Sirituba Island. (Abaetetuba, Pará State, Brazil), during spring tides, on a Mesotidal environment with semidiurnal tides. We monitored tides on Belém city at the same time, aiming to compare both regions during the same period. For our analysis, we gathered data during a year, by means of installing two pressure sensors, one on the river and one on the floodplain. Data treatment was made on Matlab software. On this context, we determined patterns of tide propagation and the river’s principal tributaries, as well as its main harmonics, phase changes and seasonality. This last is a major factor on the study area, consisting always of a rainy and a dry period. Although exposed directly to tide effects, the area subject to flooding change drastically due to seasonal fluctuation of river water levels. The region has tide ranges up to 3.6 meters on spring tides and marked asymmetry, which classifies the estuary as asymmetric.